The Olympic Games and Ritual Archery: A Comparative Study of Sport between Ancient Greece and Early China（—200 BC) - Pang, Nianliang (Πανεπιστήμιο Πελοποννήσου, 2013)
This research conducts a comparison between the Olympic Games in ancient Greece and ritual archery in early China before 200 BC, illustrating the similarities and differences between the two institutionalized cultural activities in terms of their trans-cultural comparison in regard to their origin, development, competitors, administration, process and function. Cross cultural comparison is a research method to comprehend heterogeneous culture through systematic comparisons of cultural factors across as wide domain. The ritual archery in early China and the Olympic Games in ancient Greece were both long-lived, institutionalized physical competitive activities integrating competition, rituals and music with communication in the ancient period. To compare the two programs can make us better understand the isolated civilizations in that period. In examining the cultural factors from the two programs, I find that both were originally connected with religion and legendary heroes in myths and experienced a process of secularization; both were closely intertwined with politics in antiquity, connected physical competitions with moral education, bore significant educational functions and played an important role in respective society. The administrators of the two cultural programs had reputable social rank and were professional at managing programs with systematic administrative knowledge and procedures. In addition, I also explore that there existed different concepts of the body and competition opinions between ancient Greeks and Chinese, which mainly resulted from the respective society’s geographical, political, social and educational differences. This thesis is divided into six parts. The first three parts introduce the purpose and reasons of conducting this research and present a literature review of related research achievements, as well as the research approach. The fourth part respectively presents overviews of ancient Greece and the Olympic Games before 200 BC, and early China iii and ritual archery before 200 BC. The fifth part is focused on the comparison of different cultural factors between the two cultural programs. This research arrives at the conclusions in the sixth part with an in-depth analysis and discussion. The sources for this research include the ancient classical works, books of classical studies on both China and Greece, papers from academic journals and some press and internet articles and papers.
Keywords: Olympics - Ancient Greece - China; Olympics - Ancient Greece - Chiana - History; Olympics - Study and teaching - Ancient Greece - China; Ολυμπιακοί αγώνες - Αρχαία Ελλάδα - Κίνα; Ολυμπιακοί αγώνες - Αρχαία Ελλάδα - Κίνα - Ιστορία; Ολυμπιακοί αγώνες - Μελέτη και διδασκαλία - Αρχαία Ελλάδα - Κίνα